Six Steps to Success: Lessons Learnt from Five Years of CCAFS - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
How to make 500 million farmers climate-resilient in 10 years while also reducing their agricultural emissions. Lessons learnt from five years of CCAFS.